2018
DOI: 10.1115/1.4040447
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characterization of Supersonic Jets Issuing From Double-Beveled Nozzles

Abstract: Supersonic jets at design Mach number of 1.45 issuing from circular 30 deg and 60 deg double-beveled nozzles have been investigated experimentally and numerically in the present study, with a view to potentially improve mixing behavior. Reynolds-averaged Navier–Stokes (RANS) simulations of the double-beveled nozzles and a benchmark nonbeveled nozzle were performed at nozzle-pressure-ratios (NPR) between 2.8 and 5.0, and the results are observed to agree well with Schlieren visualizations obtained from a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…It was found that, the beveled nozzle is capable of improving jet mixing and other turbulence parameters of the flow. Wu et al [14] introduced circular collar at the exit of a circular Mach 1.46 nozzle and made the double bevel cut of 30° and 60° at the collar exit, and, compared the results with non-beveled collar nozzle. The test NPR were varied between 2.8 to 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that, the beveled nozzle is capable of improving jet mixing and other turbulence parameters of the flow. Wu et al [14] introduced circular collar at the exit of a circular Mach 1.46 nozzle and made the double bevel cut of 30° and 60° at the collar exit, and, compared the results with non-beveled collar nozzle. The test NPR were varied between 2.8 to 5.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established from the literature that, most of the work on the jets from bevelled nozzles, focused on the investigation of acoustic characteristics. Also, it is clear from the literature that, the bevelled nozzles considered in the recent studies were either used as bevelled collar [12,14,15,24] or nozzles with elliptical cross-section. The present work involves computational study of the effect of nozzle exit inclination on the mixing characteristics of Mach 2.17 jet in the over-expanded conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have demonstrated that circular IO nozzles have the capability to simultaneously modify the shock structures and alter the instability characteristics of the shear layer [27,[40][41][42]. In particular, single-bevelled circular nozzles were observed to introduce thrust/jet vectoring and non-diamond shock cells [27,42] that were successful in mitigating jet screech [40] and could offer lower noise pollution in an industrial setting such as cold-spraying applications.…”
Section: Flow and Noise Control Of Supersonic Jets With Io Nozzlesmentioning
confidence: 99%
“…The jet shear layer was augmented azimuthally with asymmetric spread rates observed in the two orthogonal planes. Double-bevelled circular nozzles were observed to introduce asymmetric shock cells and jet spread rates between the two orthogonal planes, with improved overall mass flux through jet entrainment [41] and potentially favourable impact upon heat transfer levels. Single-and double-bevelled rectangular nozzles [43,44] have also been investigated and were observed to be effective in shifting the noise directivity upstream, which could further mitigate noise pollution.…”
Section: Flow and Noise Control Of Supersonic Jets With Io Nozzlesmentioning
confidence: 99%
See 1 more Smart Citation